The distinct element method-based model and its use in slope stability analysis (Journal of Nepal Geological Society, 2002)
With the advent of various modeling programs, it has become possible to build a model of a rock mass and perform extensive analysis to solve related rock engineering problems. However, there has been almost no research effort devoted to the generation of the basic input data that is needed for the faster and better model and for our improved design techniques. In light of these points, this paper describes a step-by-step procedure for the characterization of discontinuity as a means to prepare input data for a model construction based on the distinct element method (DEM). A case study is also presented in which the DEM models were constructed to carry out the slope stability analysis of an excavated rock slope. A rock reinforcement system is also designed based on the results obtained with the DEM analysis.